PENGARUH KONSENTRASI EKSTRAK ETANOL BUAH DELIMA (Punica granatum L.) TERHADAP PENINGKATAN APOPTOSIS DAN HAMBATAN INVASI SEL KANKER LIDAH MANUSIA SP-C1 IN VITRO - , Drg. Mahmud Kholifa; , drg. Supriatno, M. Kes. Ph. D., ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Oral tongue squamous cell carcinoma (OTSCC) is characterized by high degree of cell invasion and metastasis to regional and distant lymph node. Oral cancer treatment is categorized as a difficult disease to treat, although it has been to treat by holistic procedures. New strategies were needed to suppress the growth of oral cancer cell by a herbal medicine ex. Pomegranate fruit. The aim of the study is to investigate the effect of pomegranate ethanol extract on an human oral tongue cancer cell line SP-C1 through apoptosis induction and inhibition of cell invasion. The laboratory experimental study was conducted in the study. Furthermore, to detect apoptosis induction, double staining included ethidium bromide and acridine orange was carried out after 24 hours incubation. Fluorescence microscopy was used for counting the cell. Viable cells would be stained green and apoptotic cell would be stained yellow. Furthermore, to detect inhibition of cell invasion staining with keratin / hemaktosilin was carried out after 48 hours incubation. Light microscopy was used for counting the cells that pass through the membrane. Normality and homogeneity data were determined by Saphiro-wilk test and Levene test. Data was analyzed by One Way ANOVA and was continue by Post Hoc with LSD test. The result of apoptosis showed that there were significant differences apoptotic cell mean (p<0,05). Furthermore, the result of invasion cell inhibition showed that there were significant differences invasion cell inhibition mean (p<0,05). and invasion resistance of oral tongue squamous cell carcinoma cell line (SP-C1). In conclusion, pomegranate ethanol extract induced apoptosis of oral tongue squamous cell carcinoma and the increases of pomegranate ethanol extract concentration followed by the increases of apoptosis induction. Pomegranate ethanol extract also inhibited invasion of oral tongue squamous cell carcinoma and the increases of pomegranate ethanol extract concentration followed by the increases of invasion cell inhibition.